UNDERSTANDING DISABILITIES & ONLINE STUDENT SUCCESS - Betts, Kristen; Welsh, Bill; Hermann, Kelly; Pruitt, Cheryl; Dietrich, Gaeir; Trevino, Jorge; Watson, Terry; Brooks, Mike; Cohen, Alex; Coombs, Norman (Online Learning, 2013)
Approximately 11% of all postsecondary students reported having a disability in 2008. Although the percentage of students with disabilities in 2008 closely reflects the percentage reported in 2004, the U.S. Government Accountability Office states that recent legislative changes have the potential to increase the diversity and number of students with disabilities pursing higher education. To support students with disabilities enrolled in higher education and in online learning, it is important to understand disabilities and the resources students need to actively engage in their courses and to achieve their academic goals. This article includes collaborative responses from a diverse group of leaders at eight higher education institutions and organizations who work with disability services and have experience in online learning. Some of the contributors also have disabilities so the collective responses build upon research, professional experience, and personal experience. For this article, the ten contributors answered 20 questions regarding disabilities and online student success as well as provided recommended practices. This article is designed to be interactive. It includes screenshots, simulation links, video demonstrations, and resources to provide a more detailed understanding of disabilities, accessibility, and support resources. JALN readers are encouraged to interact with the simulations and to watch the demonstration videos as a way to learn more about disabilities and supporting online student success.